Performance and Emission Characteristics of Diesel Engine Fueled with Blends of Neem Biodiesel - Bist, Gagan Singh; Adhikari, Surya Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2021)
In this research, biodiesel produced from locally available Neem seed was used on the direct injection variable compression ratio (VCR) diesel engine without any modification. Neem seed, which contains 30-60% oil, was transformed into biodiesel through acid-base transesterification. The 1:6 of methanol to oil ratio, 1.2% (v/v) sulfuric acid during pretreatment and KOH as alkali catalyst for optimum yield was used. The characterization of prepared biodiesel was done according to ASTM standard. The effect of Neem biodiesel blends such as 10% Neem biodiesel and 90% conventional diesel (NBD10), 15% Neem biodiesel and 85% conventional diesel (NBD15), and 20% Neem biodiesel and 80 % conventional diesel (NBD20) were prepared and their performance and emission characteristics were studied. The test was performed at 17:1 compression ratio and 230 bar injection pressure with varying loads of 1 kg, 3 kg, 6 kg, 9 kg and 12 kg. The brake thermal efficiency (BTE), specific fuel consumption (SFC), torques and exhaust gas temperature (EGT) were analyzed on those different loads. The BTE for conventional diesel, NBD10, NBD15 and NBD20 were recorded as 8.12%, 7.23%, 6.56% and 6.23% respectively, at same loadings. These efficiencies increase with increment of load up to 31.25%, 28.96%, 27.56% and 27.35% respectively. The difference for specific fuel consumption (SFC) in pure diesel and NBD20 was recorded as 21.66% at 1 kg load whereas at 12 kg load this difference was 19.23%. The EGT for NBD20 was recorded higher than diesel for entire loading condition. The CO emission decreases with the increment of load and the proportion of biodiesel, whereas HC shows just reverse result. The smoke opacity was found better for NBD20 in comparison to conventional diesel. The performance and emission characteristics demonstrate that the blend of Neem biodiesel up to 20% with conventional diesel can be used as an alternative fuel in diesel engine without any change in the engine.